2019
DOI: 10.1038/s41598-019-40125-4
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Assembly on the Membrane Determines the HIV-1 Inhibitory Activity of Dual-Targeting Fusion Inhibitor Peptides

Abstract: Novel strategies in the design of HIV-1 fusion/entry inhibitors are based on the construction of dual-targeting fusion proteins and peptides with synergistic antiviral effects. In this work we describe the design of dual-targeting peptides composed of peptide domains of E2 and E1 envelope proteins from Human Pegivirus with the aim of targeting both the loop region and the fusion peptide domains of HIV-1 gp41. In a previous work, we described the inhibitory role of a highly conserved fragment of the E1 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Furthermore, peptide assembly on the membrane as well as recognition of its viral target on the membrane mimetic environment was studied by biophysical assays since it has been demonstrated that fusion inhibitor peptides specifically interfering with the N-terminal region of gp41 21 , need to be embedded into the membrane in order to interact properly with their viral target 22 .…”
Section: Re-e1p47 Assembles Into the Membrane Maintaining The Activementioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, peptide assembly on the membrane as well as recognition of its viral target on the membrane mimetic environment was studied by biophysical assays since it has been demonstrated that fusion inhibitor peptides specifically interfering with the N-terminal region of gp41 21 , need to be embedded into the membrane in order to interact properly with their viral target 22 .…”
Section: Re-e1p47 Assembles Into the Membrane Maintaining The Activementioning
confidence: 99%
“…Once the synthesis of the peptide sequence was completed, a fraction of the peptidyl-resin was labelled at the N-terminus with 5(6)-carboxy-tetramethyl-rhodamine (TAMRA) following the procedure described in Ref. 22 .…”
Section: Synthesis Of Peptidesmentioning
confidence: 99%
See 3 more Smart Citations